THU0253 ANTI-PM-SCL autoantibodies in polymyositis and dermatomyositis. (23rd January 2014) - Plestilova, L.; Gheorghe, K.; Lundberg, I.E.; Vincze, M.; Dankό, K.; Charles, P.; Betteridge, Z.; McHugh, N.; Vencovský, J.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are frequently accompanied by presence of autoantibodies. A correlation of anti-Jo-1 and anti-SRP antibody levels with disease activity and creatine kinase levels has been described. Recently a new anti-PM1α quantitative ELISA test detecting antibodies to the main epitope of PM-Scl-100 has become available. Objectives: To investigate the prevalence of anti-PM1α autoantibodies and association with clinical symptoms, clinical disease activity and serum CK in a multicenter myositis cohort. Methods: Two hundred and thirty eight consecutive patients with established IIM (103 DM, 99 PM, 8 JDM, 3 IBM and 25 IIM/CTD-overlap syndrome) were tested for the presence of anti PM-Scl autoantibodies by immunoblot and by immunoprecipitation. Eight additional anti-PM-Scl positive sera were also obtained. Serum levels of anti-PM1α autoantibodies were detected by ELISA kit (Dr. FOOKE Laboratorien GmbH, Neuss, DE). Clinical data were derived from the Euromyositis database (www.euromyositis.eu ). Global and organ clinical disease activities were assessed by Myositis Activity Assessment Tool (MYOACT) 10 cm visual analogue scales. Results: 19/238 (8%) patients (11 DM, 2 PM and 6 IIM/CTD-overlap syndrome (3 DM + SSc, 2 PM + SSc, 1 PM + SjS)) were positive for anti-PM-Scl in immunoblot, immunoprecipitation and anti-PM1α ELISA. 19 PM-Scl+ were 16/181 women and 3/57 men, average age 50.5 years (22.0 – 74.2) and average disease duration 3.0 years (0 – 11.6 years). Good agreement between detection tests was found. The most common clinical features among anti-PM-Scl positive patients were muscle weakness (96%), interstitial lung disease (77%), Raynaud's phenomenon (69%) and mechanic's hands (65%). One patient had a cancer. Anti-PM1α levels correlated with serum CK activity in the DM group (p=0.041, r=0.533) and with constitutional disease activity and seriousness of dysphagia in the PM group (p=0.048, r=0.768 and p=0.007, r=0.927). Furthermore longitudinal change in anti-PM1α levels correlated with HAQ scores in the whole group (p=0.016, r=0.730) and with global disease activity score in DM group (p=0.023, r=0.685), but not with other MYOACT parameters. Conclusions: Anti-PM-Scl autoantibodies are detected in 8% of patients with myositis. They are more frequent in those with DM and overlap syndromes. Presence of these autoantibodies is associated with muscle weakness, ILD, Raynaud's phenomenon and mechanic's hands. Anti-PM1α levels correlate with serum CK levels in DM and their change is correlated with change of HAQ scores in the whole group and with MYOACT scores in DM group. This suggests that the quantitative measurement of anti-PM-1α may be a useful tool in the assessment of patients with this syndrome. Disclosure of Interest: None Declared